Never fall again [large type] - Blackburn, Lynn Huggins (Blackburn, Lynn Huggins. Gossamer Falls, 2024)
"Landry Hutton has spent three years rebuilding her life behind the secure gates of The Haven, an exclusive resort on the outskirts of Gossamer Falls, North Carolina. As the artist-in-residence, and with her pottery prized by The Haven's guests, Landry is finally ready to settle in permanently. She wants to give her daughter, Eliza, a safe home to grow up in and hires former Marine Callum Shaw to handle the construction. Cal grew up in Gossamer Falls and always knew he would someday join his family's business. He longs for a family of his own but has almost given up on that ever happening. Landry is funny, gifted, and everything Cal could ever want in a partner, but he vows to keep his distance. Landry has a daughter and a past. Cal has been down that road before and barely survived when the woman he loved left, taking her two sons with her. He can't bear to lose like that again.Before construction on the house can begin, Landry's pottery is destroyed in a suspicious fire. It soon becomes clear that Landry and Eliza are in grave danger--but because of whom? Despite his best efforts to remain unattached and uninvolved, Cal knows Landry needs him--and he fears he needs her just as much"--